Identification of a Contact-Dependent Growth Inhibition (CDI) System That Reduces Biofilm Formation and Host Cell Adhesion of Acinetobacter baumannii DSM30011 Strain - Roussin, Morgane; Rabarioelina, Sedera; Cluzeau, Laurence; Cayron, Julien; Lesterlin, Christian; Salcedo, Suzana P.; Bigot, Sarah (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is a multidrug-resistant nosocomial opportunistic pathogen that is becoming a major health threat worldwide. In this study we have focused on the A. baumannii DSM30011 strain, an environmental isolate that retains many virulence-associated traits. We found that its genome contains two loci encoding for contact-dependent growth inhibition (CDI) systems. These systems serve to kill or inhibit the growth of non-sibling bacteria by delivering toxins into the cytoplasm of target cells, thereby conferring the host strain a significant competitive advantage. We show that one of the two toxins functions as a DNA-damaging enzyme, capable of inducing DNA double-stranded breaks to the chromosome of Escherichia coli strain. The second toxin has unknown catalytic activity but stops the growth of E. coli without bactericidal effect. In our conditions, only one of the CDI systems was highly expressed in the A. baumannii DSM30011 strain and was found to mediate interbacterial competition. Surprisingly, the absence of this CDI system promotes adhesion of A. baumannii DSM30011 to both abiotic and biotic surfaces, a phenotype that differs from previously described CDI systems. Our results suggest that a specific regulation mediated by this A. baumannii DSM30011 CDI system may result in changes in bacterial physiology that repress host cell adhesion and biofilm formation.